Self-powered SECE piezoelectric energy harvesting induced by shock excitations for sensor supply. (1st September 2022) - Lo, Y.C.; Shu, Y.C.
Abstract: The article studies the piezoelectric frequency up-converted energy harvester endowed with an SP-SECE (self-powered synchronized electric charge extraction) interface circuit. The harvester device comprises a piezoelectric cantilever beam whose tip magnet is impulsively excited by another magnet fixed on a rotating plate. Energy is therefore harvested by resonant vibration of a beam excited at certain discrete driving frequencies. Three aspects are discussed here, including the frequency up-conversion for conditionally resonant power, electrically induced damping for matching impedance and reducing power ripples, and SP-SECE's implementation for power extraction under shock excitations. Precisely, a theoretical model based on the Fourier decomposition of magnetic force is developed for realizing the phenomenon of frequency up-conversion. The SECE electrically induced damping is derived by considering the conversion of energy to electricity in analogy to the dissipation process of a linear mechanical damper. In addition, a novel electronic breaker is implemented for reducing the switching delay effect and enhancing the range of operating voltage. Finally, two experiments are prepared for performance evaluation. The results show the good agreement between the theoretical predictions and the experimental observations. Further, the first one with parameters close to the impedance matching criterion confirms the SECE power outperforms that based on the standard interface. The second one with the SECE electrically induced damping larger than the mechanical damping, the power ripples observed in the SECE case are much more suppressed than that based on the standard interface. Thus, the properties of load-independence and low power fluctuations make the SECE-based frequency up-converted harvester superior in powering sensor nodes operated at around 2–5 volt.